TRANSFORMASI PERAN PUSTAKAWAN LIPI SEBELUM DAN SESUDAH REORGANISASI - Mohamad Djaenudin; Tupan Tupan (Perpustakaan Nasional RI, 2020)
Purpose. This paper aims to provide an explanation of the transformation of the role of LIPI librarians before and after reorganization.Method. The study was conducted descriptively by observing and studying literature.Results and discussion. The results of the study show that prior to the reorganization, the roles of librarian are carrying out information retrieval activities related to research proposals submitted, making tracking publications to managing research results into the repository system as equal partners with LIPI researchers. In addition, they process library materials, do reference services, circulation, searching, and information packaging. After transformation, the roles of librarian are managing more research data in the repository system. The National Scientific Repository (RIN) developed by PDDI demands librarian competence to support the RIN system. Librarian competence is required to save researchers’ research data in the National Scientific Repository (RIN). The Law no. 11 of 2019 concerning the National System of Science and Technology (Sisnas Iptek) is expected to be able to regulate and become a guideline on the national research data repository system.